Sustainable Financial Literacy Policy in Breaking the Chain of Household Debts and Receivables - Fadli, Ahmad; Fawaid, Yazidul (Program Studi Ilmu Ekonomi UIN Sunan Ampel Surabaya, 2023)
This riset to explore the practices of debt and receivables that occur in households. Secondly, to formulate a sustainable financial literacy policy through digital applications and cooperative innovations, transforming the concept of conventional